2020
DOI: 10.1186/s40824-020-00193-4
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical, chemical, structural analysis and comparative release of PDGF-AA from L-PRF, A-PRF and T-PRF - an in vitro study

Abstract: Background Platelet concentrates have been popularly used in regenerative periodontal therapy as they are autologous in origin and they provide a supernatural concentration of platelets, growth factors and leukocytes. The release profile of various growth factors is considered important during the various phases of wound healing with the most important being the inflammatory phase where the release of the growth factors help in recruitment of cells and in collagen production. With the more recent modifications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
25
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 20 publications
(38 reference statements)
6
25
1
Order By: Relevance
“…Controversially, although other techniques [ 28 , 32 ] exist, the simplest way is to follow the protocols strictly using the correct centrifugation settings to obtain the correct membrane. Thus, the results obtained for L-PRF in this study (average of 0.02260 MPa) is in perfect agreement with the resistance of L-PRF published by Khorshidi et al [ 22 ] (0.20 ± 0.06 MPa), but strangely, Ravi and Santhanakrishnan (2020) [ 26 ] found an extremely higher value for L-PRF (290.076 ± 5.68 MPa). Nonetheless, the same authors also found extremely high values for A-PRF (362.565 ± 5.15 MPa), differently than obtained in this study (average of 0.04130 MPa).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Controversially, although other techniques [ 28 , 32 ] exist, the simplest way is to follow the protocols strictly using the correct centrifugation settings to obtain the correct membrane. Thus, the results obtained for L-PRF in this study (average of 0.02260 MPa) is in perfect agreement with the resistance of L-PRF published by Khorshidi et al [ 22 ] (0.20 ± 0.06 MPa), but strangely, Ravi and Santhanakrishnan (2020) [ 26 ] found an extremely higher value for L-PRF (290.076 ± 5.68 MPa). Nonetheless, the same authors also found extremely high values for A-PRF (362.565 ± 5.15 MPa), differently than obtained in this study (average of 0.04130 MPa).…”
Section: Discussionsupporting
confidence: 92%
“…Nonetheless, the same authors also found extremely high values for A-PRF (362.565 ± 5.15 MPa), differently than obtained in this study (average of 0.04130 MPa). However, this study may state that A-PRF had a higher resistance to traction than L-PRF similar to published by Ravi and Santhanakrishnan (2020) [ 26 ]; therefore, in this study, it was observed almost twice more in the average of resistance, with an extremely significant statistical difference. Concerning average traction, A-PRF also achieved a significant statistical difference compared to L-PRF.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The authors recorded the tensile strength of leukocyte platelets (L-PRF) (mean value of 0.20 ± 0.06MPa), which was significantly increased compared to the platelet rich growth factor (PRGF) group (value of 0.14 ± 0.07MPa). Ravi and Santhanakrishnan [ 47 ] investigated the mechanical properties of three different types of PRF membranes through a PRF box under the compressor and lid for 10 min. The authors recorded the tensile strength of T-PRF (titanium prepared platelet-rich fibrin), obtaining a mean value of 404.61 ± 5.92MPa which was significantly higher than that of A-PRF (362.565 ± 5.15 MPa) and L-PRF, which contained the least tensile strength (290.076 ± 5.68MPa).…”
Section: Discussionmentioning
confidence: 99%
“…The second type of platelets, platelet-rich fibrin (PRF), plays an important role in modern medicine and is used as one of the components in the production of biomaterials. As mentioned in several sources, PRF is a second-generation platelet concentrate derived from centrifuged blood [5] and, in addition to platelets, also contains white blood cells, serum and concentrated growth factors [9], such as platelet-derived growth factor (PDGF), transforming growth factor-β (TGF-β) and insulin-like growth factor 1 (IGF-I) [10]. The properties of growth factors and cytokines within the PRF are shown in Table 2.…”
Section: Abbreviation Platelet Concentrate Explanationmentioning
confidence: 99%